2018
DOI: 10.1039/c7lc00724h
|View full text |Cite
|
Sign up to set email alerts
|

Razor-printed sticker microdevices for cell-based applications

Abstract: Tape-based razor-printing is a flexible and affordable ultra-rapid prototyping approach for microscale device fabrication. However, integration of this prototyping approach into cell-based assay development has been limited to proof of principle demonstrations. This is in large part due to lack of an established or well-characterized option for biocompatible adhesive tape. Without such an option, integration of these areas will remain unexplored. Therefore, to address this critical hurdle, we characterized mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 42 publications
(48 reference statements)
0
52
0
Order By: Relevance
“…Fabrication of polystyrene-based microwells has been described in detail in several publications [25,26]. Tumor cells (5000 cells/microwell) and mesenchymal cell subtypes were seeded in adjacent compartments simultaneously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fabrication of polystyrene-based microwells has been described in detail in several publications [25,26]. Tumor cells (5000 cells/microwell) and mesenchymal cell subtypes were seeded in adjacent compartments simultaneously.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we further confirmed a lack of sensitivity to Hh inhibition in TNBC cells and a paracrine interplay between the tumor and stroma in both in vitro and in vivo models. We adapted a previously developed microscale co-culture platform [25,26] to develop a paracrine model of Hh signaling in TNBC and examined the impact of mixed and adjacent culture modalities in the tumorigenicity and transcriptional activity of the Hh pathway. The culture model was composed of TNBC human cell lines and a subset of mesenchymal cells consisting of human mammary fibroblasts (HMFs), CAFs, tumor cells that undergo epithelial–mesenchymal transition (EMT), and adipose mesenchymal stem cells (ADMSCs).…”
Section: Introductionmentioning
confidence: 99%
“…The new channel construction (Fig. 1) is made by razor-printing the channel from biocompatible double-sided adhesive tape [32] and micromilling of port holes into sheet polystyrene (#ST313300, Goodfellow Cambridge Ltd., Huntingdon, England) [33] to create a top layer with excellent clarity for imaging. The solid polystyrene channel and double-sided adhesive not only made the sensor more robust, but also allowed the sensor to be cleaned and reused.…”
Section: Methodsmentioning
confidence: 99%
“…Lithography-based techniques need clean facilities, are low-throughput for prototyping time (> 48 hrs), and require a high level of technical expertise; whereas, methods that generate heat (e.g., laser cutting) can produce toxic byproducts by the combustion process. These limitations have contributed to the lack of broad adoption and the designing of custom culture arrays among research laboratories [ 42 ]. Furthermore, methods that employ laser cutters or chemical etching generate chemical byproducts that can be toxic to cells or induce an undesirable response that can lead to artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…One way to address this fabrication barrier is to employ conventional, user-friendly, and commercially available instrumentation for surface modification of rigid polymers at the microscale level. For example, we [ 42 ], as well as others [ 44 - 46 ], successfully employed razor printing or xurography [ 43 ] to generate culture platforms made of PS at the microscale resolution. Further, they were also used for geometric patterning of electrospun substrates for cell applications [ 45 ].…”
Section: Introductionmentioning
confidence: 99%